Analysis of Village Government Policy in Improving the Quality of Education Case Study of Surabaya Student Exchange - Harianto, Dedek; Ivanna, Julia (Lembaga Penelitian dan Pendidikan Mandala, 2024)
Education inequality between villages and cities is a common issue, with villages often experiencing difficulties in accessing adequate education facilities. Village governments have an important role in improving the quality of education. This article uses qualitative research methods to understand the context, dynamics and complexities of education policies and their impact on communities. The Surabaya village government has developed an education policy that focuses on improving education in its area. This policy has shown positive impacts, but education policy evaluation is crucial to ensure sustainability and continuous improvement. Evaluations help identify weaknesses and challenges faced in implementing education policies so that improvements can be made and more effective strategies can be developed. Limited resources, facilities and competent teaching staff are some of the most significant challenges in improving the quality of education in Surabaya Village. PMM played a crucial role in the evaluation of the village's education policy, assisting in data collection and analysis, direct observation, community empowerment, and the development of recommendations for improvement. With the involvement of independent student exchanges, the village administration gains a more in-depth and comprehensive view of the effectiveness of education policies, which ultimately contributes to improving the quality of education in the village.